The subordination of black people in the United States Toni Morrison’s novel, Beloved - Wajiran Wajiran; Nur Alifah Septiani (Universitas Ahmad Dahlan, 2023)
This paper is aimed at discussing Morrison’s novel, Beloved dealing with the issues of human discrimination in the United States. Morrison is a writer who voices human values through discussions on issues of discrimination due to ethnicity, race, and skin color, especially that conducted against black people. She was instrumental in fighting for civil and political rights for black people in the United States, especially in Ohio. This study involves the theory of genetic structuralism to understand the concept of white supremacy. This is intended to see the relationship between white supremacy with the issues of social discrimination in the context of black people in the United States depicted in the novel. The issue of race and social class has always stood out in various groups of people. Even though society has progressed the issues of race, religion, and skin color still cause intergroup conflicts due to various interests. As depicted in the novel, black people are generally side-lined and considered only half human. Consequently, black citizens in the United States are associated with slavery or manual labor).